Macrodystrophia lipomatosa: four case reports - Ahmad Ibne; Wahab Shagufta; Khan Rizwan A; Chana Rajendra S (BMC, 2010)
Abstract Aim Macrodystrophia lipomatosa is a rare cause of gigantism of limb which can be confused with other common causes like congenital lymphedema. It presents usually with loss of function and cosmetic problems. Four cases are described with emphasis on clinical presentation, differential diagnoses, imaging and treatment options. Methods & Results Four patients of macrodystrophia lipomatosa were thoroughly examined and subjected to investigations. Conclusion Besides diligent clinical examination, imaging and histopathology are crucial in clinching the diagnosis.